Ressources renouvelables et croissance économique : suggestions médiévales et questions contemporaines - Mathieu Arnoux (Revue de la Régulation)
Economic history has been for a long time a meeting place for historians and economists, then a deserted land, for want of a language shared by all. It is now reinvested by model-makers, without a real interdisciplinary exchange being initiated. On the basis of examples relating to European economic history in the 11th and 12th centuries, it is proposed to reopen the dialogue between the two communities by showing that the use of different modes of demonstration does not prevent historians from adequately describing the transformation processes or economists to use it as an experimental field where to put their concepts to the test. It is also suggested that the lack of coïncidence in vocabularies is no obstacle to interdisciplinary dialogue.